Muscle force production with low and medium frequency burst modulated biphasic pulsed currents. (February 2014) - Bellew, James W.; Sanders, Kyle; Schuman, Kristen; Barton, Matt
Abstract Objective: Russian current, a medium frequency burst modulated alternating current (BMAC), is widely used for NMES, but has not been shown to elicit forces near voluntary maximum. In contrast, low frequency BMAC has been shown to produce greater force production than Russian and most recently, medium frequency burst modulated biphasic pulsed current (BMBPC) elicited greater force than Russian. Whether low frequency BMBPC yields greater force than medium frequency BMBPC is unknown. This study examined elicited forces using BMBPC with low and medium frequency carrier currents. Design: A cross-over design where percent maximal isometric knee extensor forces (%MVIF) elicited using BMBPC with low or medium kilohertz carrier frequencies were compared in 23 subjects. Perceived discomfort was also assessed. Data were compared using paired samples t-tests. Results: 98.4% of the MVIF was elicited with the low frequency BMBPC which was significantly greater (p < 0.001) than the 40.4% yielded by the medium frequency current. Cohen's d effect size of 2.146 indicated a "huge effect". Perceived discomfort of the low frequency current was 5.7/10 and was significantly greater (p < 0.001) than the medium frequency current (3.6/10). Conclusion: BMBPC with low frequency carrier current elicits forces approximating maximal volitional force. These findings offer new evidence with strong clinical implications when using NMES.